Tracking elderly Alzheimer's patient using real time location system - Abuhan, Mohd Fadhil; Mohamed Shariff, Abdul Rashid; Ghiyamat, Azadeh; Mahmud, Ahmad Rodzi (General Healthcare Inc., 2013)
Alzheimer Disease (AD) has major implications on patient safety and care. The elderly Alzheimer’s patient encounters risk of losing their memory capabilities and are unable to live a normal life accordingly. The short memory may lead them to wander aimlessly and danger. Hence, the Alzheimer’s patients need to be monitored closely to ensure their safety. In this paper, an assistive technology tool called Alzheimer’s Real Time Location System (ARTLS) was developed. The system tracks all the patients instantaneously in real time and helps in analyzing patient spatial movement for enhancing their care management. As a general result, ARTLS relieves the caregiver’s burden and enhances patient’s safety by close monitoring of the wandering movements of the patients in real time.